Where Programming, Ops, AI, and the Cloud Are Headed in 2021 - Loukides, Mike; Loukides, Mike (O'Reilly Media, Inc., 2021)
In this report, we look at the data generated by the O'Reilly online learning platform to discern trends in the technology industry: trends technology leaders need to follow.